2017
DOI: 10.5812/jjm.55616
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Efficacy of Positively Charged Imidazolium-Based Silver Nanoparticles in Enterococcus faecalis Using Quantitative Real-Time PCR

Abstract: Background: Nanoparticles are made by different methodologies, which can affect the particle's features. Recently, imidazoliumcoated silver nanoparticles with a positive surface charge (PC Im-based AgNPs) have revealed favorable results as a root canal disinfectant. However, the antibacterial potency of these particles against biofilm form of Enterococcus faecalis, as the most resistant organism to eliminate in endodontic treatment, has not been investigated. It can be noted that removing this microorganism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
5
14
0
Order By: Relevance
“…To better investigate the chemical disinfecting ability of the tested irrigants, the contaminated root canals were only treated by passive irrigation without mechanical debridement to avoid additional variable, which could be different from the clinical situation. The present study revealed that 1% NaOCl had a powerful antibacterial effect against intracanal E. faecalis biofilm, which is in accordance with the results of previous studies (Del Carpio‐Perochena et al 2011, Guerreiro‐Tanomaru et al 2014, Nabavizadeh et al 2017, Bolhari et al 2018, Rodrigues et al 2018). Extracellular polysaccharide matrix secreted by bacteria in biofilms could prevent AMPs penetration and requires a longer time of interaction to eliminate biofilm (Mai et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…To better investigate the chemical disinfecting ability of the tested irrigants, the contaminated root canals were only treated by passive irrigation without mechanical debridement to avoid additional variable, which could be different from the clinical situation. The present study revealed that 1% NaOCl had a powerful antibacterial effect against intracanal E. faecalis biofilm, which is in accordance with the results of previous studies (Del Carpio‐Perochena et al 2011, Guerreiro‐Tanomaru et al 2014, Nabavizadeh et al 2017, Bolhari et al 2018, Rodrigues et al 2018). Extracellular polysaccharide matrix secreted by bacteria in biofilms could prevent AMPs penetration and requires a longer time of interaction to eliminate biofilm (Mai et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The nanoparticles may have a positive, negative or neutral charge on their surface. The interaction of these three types of charge with the electric charge present on the surfaces of the bacteria in some cases seems to be the most important factor that determines the antimicrobial activity of the nanoparticles [24]. For example, Abbaszadegan et al tested the antimicrobial activity of silver nanoparticles with a positive, negative, and neutral charge on Gram-positive ( Streptococcus pyogenes, Streptococcus mutants, and Staphylococcus aureus ) and Gram-negative ( Proteus vulgaris and Escherichia coli ) species.…”
Section: Defense Mechanisms Against the Surface Charge Of Metal Anmentioning
confidence: 99%
“…Long-term or secondary dental caries may lead to pulpitis and apical periodontitis which are mainly caused by bacteria and their products. Enterococcus faecalis ( E. faecalis ) is mainly responsible for reinfections after root canal therapy [43,44,45]. Complex root canal anatomy makes the complete microbial cleanup particularly difficult, even with a thorough root canal preparation and filling [46,47].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%
“…The application of NPs has attracted researchers’ attention [43,48,49,50,51]. Biosynthesized AgNPs had an antimicrobial ability against E. faecalis [52,53,54].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%